Modelling the biological significance of behavioural change in coastal bottlenose dolphins in response to disturbance. (12th March 2013) - New, Leslie F.; Harwood, John; Thomas, Len; Donovan, Carl; Clark, James S.; Hastie, Gordon; Thompson, Paul M.; Cheney, Barbara; Scott‐Hayward, Lindesay; Lusseau, David; Costa, Daniel
Summary Behavioural change in response to anthropogenic activities is often assumed to indicate a biologically significant effect on a population of concern. Disturbances can affect individual health through lost foraging time or other behaviours, which will impact vital rates and thus the population dynamics. However, individuals may be able to compensate for the observed shifts in behaviour, leaving their health and thus their vital rates and population dynamics, unchanged. We developed a mathematical model simulating the complex social, spatial, behavioural and motivational interactions of coastal bottlenose dolphins (Tursiops truncatus) in the Moray Firth, Scotland, to assess the biological significance of increased rate of behavioural disruptions caused by vessel traffic. We explored a scenario in which vessel traffic increased from 70 to 470 vessels a year in response to the construction of a proposed offshore renewables' facility. Despite the more than sixfold increase in vessel traffic, the dolphins' behavioural time budget, spatial distribution, motivations and social structure remain unchanged. We found that the dolphins are able to compensate for their immediate behavioural response to disturbances by commercial vessels. If the increased commercial vessel traffic is the only escalation in anthropogenic activity, then the dolphins' response to disturbance is not biologically significant, because the dolphins' health is unaffected, leaving the vital rates and population dynamics unchanged. Our results highlight that behavioural change should not automatically be correlated with biological significance when assessing the conservation and management needs of species of interest. This strengthens the argument to use population dynamics targets to manage human activities likely to disturb wildlife.